A 23-Year-Old Man With Multisystem Inflammatory Syndrome After Mild COVID-19 - Alexander C. Razavi MPH; Jonathan L. Chang MD; Aimee Sutherland MD, MPH; Anjali Niyogi MD, MPH; Geraldine E. Ménard MD (SAGE Publishing, 2020)
We present the case of a young obese patient with recent COVID-19 (coronavirus disease 2019) who developed multisystem inflammatory syndrome (MIS) 1 month after spontaneous resolution. A 23-year-old African American man was admitted with a 1-week history of worsening fatigue, myalgias, headache, and dyspnea. Nasopharyngeal swab for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was negative by polymerase chain reaction; however, the patient was febrile and had leukocytosis, elevated troponin I, transaminitis, and acute kidney injury. Bedside echocardiogram showed decreased left ventricular ejection fraction (40% to 45%) and global hypokinesis in the setting of a type II non-ST segment myocardial infarction. Despite being on broad spectrum antibiotic therapy, the patient's clinical condition continued to worsen. The patient was then empirically treated for MIS with intravenous immunoglobulin and methylprednisolone, which led to a rapid resolution of fever and laboratory abnormalities. This case highlights that MIS associated with COVID-19 may present in patients above the age of 21 years and can occur with a delayed onset after mild illness in those with no previous oxygen requirement or hospitalization during SARS-CoV-2 infection.